2021
DOI: 10.5194/nhess-21-1685-2021
|View full text |Cite
|
Sign up to set email alerts
|

Changes in drought features at the European level over the last 120 years

Abstract: Abstract. In this study we analyze drought features at the European level over the period 1901–2019 using three drought indices: the standardized precipitation index (SPI), the standardized precipitation evapotranspiration index (SPEI), and the self-calibrated Palmer drought severity index (scPDSI). The results based on the SPEI and scPDSI point to the fact that Central Europe (CEU) and the Mediterranean region (MED) are becoming dryer due to an increase in the potential evapotranspiration and mean air tempera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 49 publications
3
45
1
Order By: Relevance
“…Climate change‐induced extreme events, such as prolonged summer droughts or heatwaves, have become more frequent in recent years and are projected to increase in Central Europe (Füssel et al . 2017; Ionita & Nagavciuc 2021; Seneviratne et al . 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change‐induced extreme events, such as prolonged summer droughts or heatwaves, have become more frequent in recent years and are projected to increase in Central Europe (Füssel et al . 2017; Ionita & Nagavciuc 2021; Seneviratne et al . 2021).…”
Section: Introductionmentioning
confidence: 99%
“…With increased temperatures and altered rainfall patterns, the risk of droughts is increasing in Europe. 33 This indicator tracks the frequency of extreme to exceptional seasonal droughts in Europe (1951–2020) with the Standardised Precipitation–Evapotranspiration Index (SPEI6) 34 , which accounts for the impact of precipitation and potential heat-related evapotranspiration. Extreme-to-exceptional drought events were defined as SPEI6 values of –1·6 or less, accumulated over April to September.…”
Section: Section 1: Climate Change Impacts Exposures and Vulnerabilitiesmentioning
confidence: 99%
“…Previous studies found divergence in trends of drought characteristics between SPI and SPEI in observations (Stagge et al, 2017;Karimi et al, 2020;Ionita and Nagavciuc, 2021), historical climate simulations (Chiang et al, 2021) and future climate projections (e.g. Arnell and Freeman, 2021;García-Valdecasas Ojeda et al, 2021;Wang et al, 2021;Ogunrinde et al, 2021), with SPEI indicating increased drying compared to SPI.…”
Section: Differences Between Spi and Spei Projectionsmentioning
confidence: 95%